TWO STAGES OF THE CENOZOIC ALKALINE-BASALT VOLCANISM IN THE DARKHAD DEPRESSION (NORTHERN MONGOLIA) – GEOCHRONOLOGY, GEOCHEMISTRY, AND GEODYNAMIC CONSEQUENCES - S. S. Tsypukova; A. B. Perepelov; E. I. Demonterova; A. V. Ivanov; S. I. Dril; M. I. Kuzmin; A. V. Travin; Yu. D. Shcherbakov; M. Yu. Puzankov; S. V. Kanakin (Геодинамика и тектонофизика, 2022)
The isotopic data showed that there are two stages distinguished in the Cenozoic history of the Darkhad depression volcanic activity, the Late Oligocene initial stage (~28.0–26.6 Ma) and the final Late Miocene – Early Pliocene stage (~5.8–4.2 Ma). It has been stated that the rocks of the initial stage are only represented by trachybasalts; however, among the final-stage basaltoids there are series of shield-volcano hawaite-basanite-phonotephrite rocks and compex trachybasaltic "valley" lava flows, the formation of which is the last stage in the territorial volcanic evolution. It has been shown that the initial-stage trachybasaltic andesites are characterized by their enrichment of TiO2, P2O5, Sr, Zn, Ga and low concentrations of Al2O3, MnO, CaO, Sc and HREE (La/Yb=27.2–30.2). Basaltoids of the final stage have a similar rare-element distribution and show an increase in the contents of TiO2, Al2O3, P2O5, LILE, HFSE, Th, U and in the degree of fractionation of REE (La/Yb from 12.2 to 20.9) towards the rocks alkalinity enhancement. Modeling of eclogite, pyroxenite and peridotite melting processes in the La/Yb – Sm/Yb system shows that trachybasaltic andesite melts could be formed at ~7–8 % melting of eclogitic matter or at ~10–11 % melting of Grt-containing pyroxenites, with trachybasalt formed at ~3 % melting of Grt-containing peridotites. The composition distribution of rocks in coordinates (Mg# – Fe/Mn) indicates that the parental magmas are the initial-stage trachybasaltic andesite magmas as well as the Early Pliocene trachybasaltic "valley" lava flows. Sr, Nd, Pb isotope characteristics of the Darkhad depression basaltoids show significant shift of isotopic ratios in time towards the relatively enriched mantle as compared with the depleted MORB mantle. The initial formation of trachybasaltic andesite melts occurred in the Late Oligicene at the pre-rift stage of the territory development involving metasomatized mantle matter, with the pyroxenite or eclogite component contained in the magma formation source. The origin of trachybasalt magmas of the final stage is associated with the processes of decompression melting of peridotites in a weakly metasomatized lithospheric mantle at the rift stage of the Darkhad structure development.